2019
DOI: 10.1016/j.bpj.2018.11.2649
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interactions of IAPP

Abstract: A characteristic property of intrinsically disordered and unfolded proteins is their high molecular flexibility, which enables the exploration of a large conformational space. We present neutron scattering experiments on the structure and dynamics of the intrinsically disordered myelin basic protein (MBP) and the chemically denatured bovine serum albumin (BSA) in solution. Small-angle neutron scattering (SANS) experiments allowed us to gain information of structural aspects of MBP and denatured BSA as response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Christensen and Schiott combined a coarse-grained model with umbrella sampling and MD simulations to study the binding of hIAPP on ganglioside-rich membranes. 303 Their multi-scale simulations suggest that hIAPP peptides localize in the membrane regions with higher local concentration of gangliosides because electrostatic interactions favour the association of the cationic hIAPP peptides and the anionic headgroup of the gangliosides.…”
Section: Scollo Et Al Investigated Hiapp Insertion In a Popc (Phosphatidylcholine) Bilayer Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Christensen and Schiott combined a coarse-grained model with umbrella sampling and MD simulations to study the binding of hIAPP on ganglioside-rich membranes. 303 Their multi-scale simulations suggest that hIAPP peptides localize in the membrane regions with higher local concentration of gangliosides because electrostatic interactions favour the association of the cationic hIAPP peptides and the anionic headgroup of the gangliosides.…”
Section: Scollo Et Al Investigated Hiapp Insertion In a Popc (Phosphatidylcholine) Bilayer Bymentioning
confidence: 99%
“…A single molecule of IAPP has been simulated in the presence of a lipid bilayer or without membrane to compare the monomeric state of hIAPP and pIAPP or rIAPP . In μs-long MD simulations Qiao et al observed transient α-helical and β-sheet structures of monomeric hIAPP during adsorption to the surface of a POPG (palmitoyloleoylphosphatidylglycerol) bilayer .…”
Section: High-resolution Structures Of Iappmentioning
confidence: 99%
“…However, additional experimental data are needed to propose more accurate models depicting the role of exosomes in IAPP amyloidogenesis and diabetes development. Molecular simulations of membrane-bound hIAPP from different species have been carried out [200][201][202] including the non-toxic, non-amyloidogenic rIAPP [203]. Molecular dynamics (MD) simulations revealed short-lived α-helical and β-sheet structures throughout IAPP adsorption onto an anionic POPG (palmitoyl oleoyl phosphatidylglycerol) surface of a lipid bilayer [201].…”
Section: Iapp-membrane Interactionsmentioning
confidence: 99%
“…Both simulations and experiments demonstrated that IAPP insertion into zwitterionic membranes is assisted by non-vesicular lipids that are present in solution at their critical micellar concentration (cmc). Other authors have adopted coupled coarse-grained/umbrella sampling molecular dynamics simulations to investigate the interactions of hIAPP with ganglioside-rich membranes [200]. These simulations indicate that hIAPP locate in ganglioside-rich membrane regions due to electrostatic interactions promoting adhesion of cationic hIAPP peptides with anionic gangliosides.…”
Section: Iapp-membrane Interactionsmentioning
confidence: 99%